Profile of the Implementation of Guided Inquiry-Based Interactive E-Module in Science Learning - Imas Nur Mazidah; Wahono Widodo; Tukiran (Studies in Philosophy of Science and Education, 2023)
Research was conducted to describe and analyze the implementation of guided inquiry model of science learning in Indonesia. This research method uses qualitative methods with using secondary data. The sample in this research is 24 articles published in international and national journals. Based on the analysis of 24 articles on science learning using Interactive E-module with guided inquiry model in Indonesia, it can be seen that the guided inquiry model has a positive impact on student learning outcomes, it can improve students' critical thinking skills, students' science process skills, students' scientific literacy, aspects of problem solving skills, and also students' understanding of concepts. Based on that articles published exactly optimal it able combine with media or other methods example for interactive e-module, students won't be confused if they get the instruction from the teacher, and it require a lot of preparation and learning duration. Based on a literature review on the implementation of guided inquiry-based modules in 2016-2022 that has been implemented, it can be concluded that the guided inquiry model has a positive impact on science learning. Therefore, now researchers developed an interactive e-module based on guided inquiry in science learning to improve science process skills.